The Role of British Council in Training the Primary School Teachers in English as Medium of Instruction in Khyber Pakhtunkhwa, Pakistan - Shabir Ahmad; Iffat Ara Hussain; Akhtar Ali (International Journal of Theory and Application in Elementary and Secondary School Education, 2020)
The present study would explore the changes the training program brings in Primary School Teachers in Khyber Pukhtunkhawa. The objective of the study was to explore the changes the training program brought in Primary school teachers. The primary school teachers who successfully completed grade III training English as Medium of Instruction in Khyber Pukhtunkhawa were the population of the study. The study was delimited to male primary school teachers of the three districts namely Mardan, Peshawar and Swabi of Khyber Pakhtunkhwa. The target population was 1947 male primary school teachers from which a sample of 330 primary school teachers was selected. The data was collected through a self-developed questionnaire of five Likert scale and fed into the SPSS Version 16 and analyzed through percentage and chi-square. The results of the study illustrated that after the training the primary school teachers were able to use English as Medium of Instruction. The study recommended that such trainings should be arranged for teachers to improve their skills of using English as Medium of Instruction